Pengukuran Pengukuran Regangan pada Ketahanan Struktur Plat Besi Menggunakan Sensor Strain Gauge - Muthiana Gusnam; Refika Ningsih; Dessy Oktani; Kamarudin; Rahmi Mahdaliza; Muhammad Jaka Wimbang Wicaksono; Ahmad Syafi’i; Aditya Gautama; Eka Mutia Lubis; Ardian Budi Kusuma Atmaja (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2026)
Steel plates are widely used in structural applications because of their ability to maintain structural form and their high tensile strength, which allows them to withstand significant loads in construction. This study presents the development of a monitoring system designed to measure strain in steel plate structures using strain gauge sensors. A theoretical comparison based on the elastic modulus of steel plates was employed to calculate stress, strain, and elongation under varying loads. The strain values recorded by the sensors are processed through an ESP32 microcontroller and displayed on an LCD screen for real-time observation. To enhance safety, the system is equipped with a buzzer and indicator lights that provide early warnings when the applied load exceeds a specified threshold. Experimental results show an average measurement error of only 2,98% compared to theoretical values, confirming the system’s accuracy and reliability. The proposed system offers a cost-effective and practical solution for infrastructure maintenance and supports the early detection of structural strain in steel plates.